INTEGRASI NILAI-NILAI SPIRITUAL DALAM MATERI RELASI - Kusno Kusno; Marsigit Marsigit (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2018)
The purpose of this study was to express spiritual values in mathematic learning of Relations. This study was a qualitative research with a case study method with a grounded theory approach. The research subjects were mathematics teachers and 2ndstudents of MTs 1 Banyumas who were selected using purposive sampling technique. Methods of data collection through in-depth interviews, observation, and document studies. Data were analysed with inductive method and discribed with narative. The results showed that the spiritual values in relation material can be extracted from the ontological concept of relations. Spiritual values in Relationships philosophically contribute to the development of the structure of human life